GREEN TAX INCENTIVES AND CORPORATE SUSTAINABILITY PERFORMANCE: INTERNATIONAL EVIDENCE - Jabida Latuamury; Dwi Kriswantini (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study aims to analyze the relationship between green tax incentives and sustainability performance based on international empirical evidence. Increasing global pressure on climate change, energy transition, and the achievement of the Sustainable Development Goals (SDGs) has prompted various countries to implement environmentally-based fiscal policies to encourage more sustainable business practices. The method used in this study is a literature review, examining various scientific articles, policy reports, and international academic publications that discuss the implementation of green tax incentives and their impact on environmental, social, and corporate governance aspects. The results of the study indicate that green tax incentives, such as tax credits, tax allowances, tax holidays, and super deductions for environmentally friendly investments, contribute positively to encouraging the adoption of green technology, increasing energy efficiency, reducing carbon emissions, and strengthening companies' Environmental, Social, and Governance (ESG) practices. Furthermore, these incentives can reduce investment barriers to sustainable innovation and enhance long-term corporate competitiveness. However, the effectiveness of these policies is strongly influenced by the quality of governance, regulatory certainty, institutional capacity, and the level of corporate awareness of the sustainability agenda.